Fifty Years of Art : The Hiscox Collection 1970-2020. - Hintz, Whitney; Smith, Laura; Storey, Grace (London : Whitechapel Gallery : Hiscox Collection, 2020)
Adnan, Etel ; Almond, Darren ; ; Burtynsky, Edward ; Coventry, Keith ; Doherty, Willie ; Goldin, Nan ; Goudal, Noemie ; Hockney, David ; Hodgkin, Howard ; Katz, Alex ; Keenleyside, Simon ; Nagle, Ron ; Oppenheim, Yves ; Paolozzi, Eduardo ; Pasmore, Victor ; Tal R ; Ryan, Kathleen ; Ruff, Thomas ; Sahib, Prem ; Steinbach, Haim ; Wilding, Alison ; Abad, Pio ; Allen, Phillip ; Apfelbaum, Polly ; Baldessari, John ; Barrada, Yto ; Batchelor, David ; Blaeu, Willem ; Boetti, Alighiero ; Chaimowicz, Marc Camille ; Christo and Jeanne-Claude ; Soto Climent, Martin ; Cole, Willie ; Heitor Cortesão, Gil ; Cranston, Andrew ; Davis, Noah ; de Lima, Maria ; Du Pasquier, Nathalie ; Fowler, Lilah ; Gordon, Daniel ; Hamilton, Richard ; Kurant, Agnieszka ; Lambie, Jim ; Lanyon, Peter ; Leibovitz, Annie ; LeWitt, Sol ; Lorenzato, Amadeo Luciano ; Martinez, Eddie ; Milner, Nancy ; Miró, Joan ; Morris, Sarah ; Mosse, Richard ; Neubart, Malgorzata ; Núñez, Jorge Pedro ; Ofili, Chris ; Pepperstein, Pavel ; Picasso, Pablo ; Pietromarchi, Benedetto ; Reynolds, Abigail ; Riddy, John ; Spota, Jeni ; Wadden, Brent ; Zitouni, Ali
Hiscox Collection. Accelerate your escape, Whitechapel Gallery, London, 25 August 2020 - 3 January 2021 ; Hiscox Collection. Desde el Salón (From the Living Room), Whitechapel Gallery, London, 13 January - 18 April 2021
boek